An Underwater Glider with Muscle—Actuated Buoyancy Control and Caudal Fin Turning - Biao Wang; Yishan Chen; Yige Wu; Yi Lin; Sijie Peng; Xiaohan Liu; Shijian Wu; Sicong Liu; Juan Yi; Panagiotis Polygerinos; Zheng Wang (Machines, 2022)
Underwater robotic gliders exploit gravity and buoyancy for long-distance cruising with ultra-low energy consumptions, making them ideal for open ocean surveying operations. However, the gliding-based motion generation principle also prevents their maneuverability, limiting their use in the short distances that are usually encountered in harbors or coastal scenarios. In this work, an innovative underwater glider robot is developed, enabling maneuverability through the introduction of an efficiently actuated caudal fin with bidirectional turning capabilities. In addition, modular actuator units, based on soft actuated materials, are integrated to control pitch angle by dynamically shifting the center of mass from the center of buoyancy. As a result, the high energy efficiency feature of the gliders is maintained, while high maneuverability is also achieved. The design concept, modeling of key components, and framework for control are presented, with the prototyped glider tested in a series of bench and field trials for validation of its motion performance.